Pengangkatan Anggota Aktif TNI Sebagai Sekretaris Kabinet Dalam Perspektif UU Nomor 34 Tahun 2004 dan Fiqih Siyasah - M Fachri Sabrian; Mhd Yadi Harahap (Universitas Cokroaminoto Yogyakarta, 2026)
The research aims to analyze the legality and constitutional implications of appointing active members of the Indonesian National Armed Forces (TNI) as Cabinet Secretary from the perspective of Law Number 34 of 2004 concerning the TNI and fiqih siyasah. This doctrinal legal research uses legislative, conceptual, and comparative approaches. Data are from manuscript studies of legal materials and fiqih siyasah. The results show that the appointment of active military personnel to strategic civilian positions is contrary to the spirit of military reform and the principle of civilian supremacy. From the perspective of fiqih siyasah, this policy violates the principles of al-'adalah, al-amanah, and al-shura. As a result, it has the potential to undermine bureaucratic accountability, create conflicts of interest, and threaten the democratization of government. Consistency of legislation, strengthening of sharia-based governance ethics and the constitution to maintain the integrity of the state power structure are needed.